Software Engineering Evolution: The History Told by ICSE - Sousa, Bruno L.; Ferreira, Mívian M.; Ferreira, Kecia A. M.; Bigonha, Mariza A. S. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2019: Anais do XXXIII Simpósio Brasileiro de Engenharia de Software, 2019)
Software Engineering knowledge has continuously grown at a very high speed. In this work, we aim to provide a perspective on how the body of knowledge of Software Engineering has evolved. For this purpose, we analyzed data of 3,300 works published from 1988 to 2018 in one of the most important conferences on Software Engineering, the International Conference on Software Engineering (ICSE). We identified the main topics investigated in Software Engineering and how the investigation of those topics has evolved over the time. The results bring a compilation of Software Engineering evolution that may be of value to the software community.